1984
DOI: 10.1016/s0022-5347(17)49466-3
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopy Detects Bacteria within Infection Stones

Abstract: The viability and location of bacteria within infection stones were investigated. Many stones were infected with urea-splitting bacteria, such as Proteus mirabilis and Pseudomonas aeruginosa. Large numbers of bacterial impressions and bodies were found in the interstices surrounded by crystals of apatite and struvite from the nuclei to the peripheral layers. The presence of bacterial colonies even in the nuclear portion of the stones suggests that bacteria participate in the initial stone formation as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…It is proposed that the weaker binding is enough for concentration, but facilitates the release for crystal growth (Dumanski et al 1994). Stone formation is facilitated by additional bacterial growth or interactions between stones, and the stone eventually comprises a matrix with imbedded bacteria (Nickel et al 1987;McLean et al 1989;Takeuchi et al 1984). Studies by Li et al used P. mirabilis cells constitutively expressing green fluorescent protein (GFP) to visualize cells within urinary stones in a mouse model of urinary tract infection.…”
Section: Infectious Urinary Stonesmentioning
confidence: 99%
“…It is proposed that the weaker binding is enough for concentration, but facilitates the release for crystal growth (Dumanski et al 1994). Stone formation is facilitated by additional bacterial growth or interactions between stones, and the stone eventually comprises a matrix with imbedded bacteria (Nickel et al 1987;McLean et al 1989;Takeuchi et al 1984). Studies by Li et al used P. mirabilis cells constitutively expressing green fluorescent protein (GFP) to visualize cells within urinary stones in a mouse model of urinary tract infection.…”
Section: Infectious Urinary Stonesmentioning
confidence: 99%
“…Struvite (magnesium ammonium phosphate hexahydrate) is one of the major components of urinary tract concrements, and it is found in 15-20% of renal calculi [6,7], Ureolytic organisms are often isolated from surgi cally excised struvite calculi [6,8,9], but isolation of nonureolytic has also been reported [10], On the other hand, studies in vitro have shown the importance of ureolytic bacteria and urease activity in the generation of struvite and apatite [2,11,12], In these experiments no crystal formation was observed in cul tures of nonureolytic bacteria. But in general all these experiments have been performed with strains belonging to different genera.…”
Section: Introductionmentioning
confidence: 99%
“…The deep crevices of the stone may shield bacteria from clearance by host immune cells while allowing access to nutrients. Takeuchi et al reported the presence of P. mirabilis in areas ranging from the nuclei to the peripheral layers in struvite stones (26). Bacteria encased in stones may be protected from antibiotic killing and thus cause persistent or recurrent infections.…”
mentioning
confidence: 99%